Cardiopulmonary Clinical Case Scenario - Charlotte Rhodes; Maria Sheakley (Association of American Medical Colleges, 2008)
Abstract This case was written to integrate cardiopulmonary material from the anatomy (embryology) and physiology departments for first-year medical students. The case is intended for use in a team-based learning format, and was written to generate group and class discussion regarding a diagnosis. The case provides basic clinical information about patent ductus arteriosus and the cardiovascular and pulmonary physiological concepts surrounding the defect.